Uranium. No. 06. Murray Piloski discusses Brinex activities in Labrador - Memorial University of Newfoundland. Extension Service (Community Learning Centre, 1977)
Murray J. Piloski, Manager, Environment and Site Operations of Brinko, talks about the work done to date on the Brinex uranium explorations in Labrador.